2020
DOI: 10.1007/s00167-020-06328-3
|View full text |Cite
|
Sign up to set email alerts
|

Periimplant osteolysis does not affect the outcome of rotator cuff repair: a systematic review and meta-analysis

Abstract: PurposeThe goal of this study was to perform a systematic review and meta‐analysis to compare the clinical and radiologic outcomes of rotator cuff repair, depending on the presence of developed periimplant osteolysis (PIO) after using suture anchors. MethodsThe electronic databases of MEDLINE, EMBASE, and the Cochrane Central Register of Controlled Trials were searched for articles published up until October 2019 to find relevant articles comparing the outcomes of rotator cuff repair between the periimplant os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Pilge et al have reported that in rotator cuff repair surgery using Bio-Corkscrew (Arthrex, Naples, Florida, United States), bone hole enlargement was observed in 22 out of 70 cases after more than 24 months of follow-up [ 9 ]. Lee et al reported that there was no difference in clinical outcomes or reoperation rates with or without bone hole enlargement in rotator cuff repair surgery using absorbable anchors [ 10 ]. Tompane et al reported that cyst formation with the use of soft anchors in Bankart repair was infrequent, but the cysts expanded over time [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pilge et al have reported that in rotator cuff repair surgery using Bio-Corkscrew (Arthrex, Naples, Florida, United States), bone hole enlargement was observed in 22 out of 70 cases after more than 24 months of follow-up [ 9 ]. Lee et al reported that there was no difference in clinical outcomes or reoperation rates with or without bone hole enlargement in rotator cuff repair surgery using absorbable anchors [ 10 ]. Tompane et al reported that cyst formation with the use of soft anchors in Bankart repair was infrequent, but the cysts expanded over time [ 11 ].…”
Section: Discussionmentioning
confidence: 99%